Washed rice water as a potential liquid fertilizer and soil amendment for crop productivity - Nabayi, Abba (2023)
Wastewater from washed rice water (WRW) is often recommended as liquid fertilizer in most Asian countries. However, WRW studies are very scarce and they lack scientific rigor, particularly on how the rice washing intensity, volumetric water-to-rice ratio (W:R), the kind and type of bacteria in the WRW after fermentation, and condition of the WRW before use could influence both the WRW nutrients and its effect on plant growth. Therefore, a series of experiments were carried out with the following objectives: 1) to determine the nutrient contents of WRW forms (fermented and unfermented) as affected by different washing intensities, rice to water ratio and fermentation periods, 2) to isolate, characterize, and identify the bacteria in WRW at different fermentation periods; 3) to evaluate the effect of continuous WRW application on the nutrient leaching losses and retention of three different soil textures and; 4) to evaluate the effects of the continuous use of fresh and fermented WRW under glasshouse conditions by examining their effects on the growth and yield of choy sum (Brassica chinensis var. parachinensis) and the soil chemical properties and microbial population of three contrasting soil textures over three planting cycles and, 5) to evaluate the best WRW (based on the glasshouse study) as a nutrient source and soil amendment on the growth and yield of choy sum in the field. The results showed that all nutritional elements of WRW increased (except P, Mg, and Zn) with longer fermentation and with higher W:R. Beneficial microbes were isolated from the WRW at different fermentation periods and identified using gene sequencing as Bacillus velezensis, Enterobacter spp., Pantoea agglomerans, Klebsiella pneumoniae and Stenotrophomonas maltophilia. The identified isolates were positive to atmospheric nitrogen fixation, P- and K- solubilization, catalase enzyme and phytohormone production. 3-day fermented WRW had the significantly higher bacterial population (2.12 × 108 CFU mL−1), N fixation, P and K solubilizations, and phytohormone production, which all decreased with longer fermentation periods. Because WRW contains nutrients, a leaching study carried out indicated that the sandy clay loam soil had the higher cumulative leaching of K, P, Mg, Ca, NH4-N, and NO3—N of 666, 378, 140, 51, 45, and 27 mg L-1, respectively, while the clay and silt loam mostly had a comparably lower nutrients leaching. The WRW was further evaluated in glasshouse with treatments as follows: 3-day fermented WRW (F3), 450 kg ha-1 of NPK 15: 15: 15 (NPK), fresh WRW (F0), and tap water as control (CON), and three soil types: sandy clay loam, clay, and silt loam soils were arranged factorially in a randomized completely block design. Choy sum used as the test crop was grown in the same soils receiving similar treatments consecutively for three planting cycles. The results showed that NPK and F3 had the significantly higher plant height, number of leaves, leaf fresh and dry weight, and total leaf area by 5-61% as compared with the other treatments in all the planting cycles. Comparable plant growth and yield in F3 with NPK could be attributed to the beneficial bacteria in the WRW in addition to the nutrients present. The soil bacterial population increased with the continuous planting cycle for all treatments. The F3 had 73 % increase in soil bacterial population while the NPK had 25 % increase relative to their previous planting cycles. Based on the higher performance of the F3, it was selected for field evaluation. The field experiment had four treatments: 3-day fermented WRW (RW3), 450 kg ha-1 of NPK 15: 15: 15 (NPK), 50 % NPK with RW3 (NPK+RW3), and tap water (CON), which were replicated thrice, and the experiment was conducted for three consecutive planting cycles on the same soil and choy sum was used as the test crop. The results showed that the NPK+RW3 had the significantly higher crop yield, nutrient contents, and nutrients uptake by 4-53 %, 9-25 %, and 36-71 %, respectively. The soil and plant nutrient contents and uptake were significantly positively correlated with one another. The presence of nutrient and beneficial microbes in the fermented WRW gave rise to the higher choy sum’s growth. The continuous increase in the plant growth with successive planting cycles indicated the carryover effects of both theiiutriaents and beneficial bacteria applied into the soil through the fermented WRW application. Overall, combining the 50 % NPK recommended rate with RW3 gave a better growth and yield in the field, while the use of either NPK or fermented WRW alone had a comparable plant yield in both the glasshouse and the field. Therefore, addition of organic amendments to improve the water and nutrient retention of the soil for agricultural practices is encouraged; thereby, minimizing the nutrient leaching losses of the soils. This research suggests the use of 3-day fermented WRW to derive the microbial benefits contained in the WRW, and better WRW performance is obtained when combined with NPK fertilizer.